2021
DOI: 10.3389/fphys.2021.752768
|View full text |Cite
|
Sign up to set email alerts
|

Reference Gene Selection for Normalizing Gene Expression in Ips Sexdentatus (Coleoptera: Curculionidae: Scolytinae) Under Different Experimental Conditions

Abstract: Ips sexdentatus (Coleoptera: Curculionidae: Scolytinae) is one of the most destructive and economically important forest pests. A better understanding of molecular mechanisms underlying its adaptation to toxic host compounds may unleash the potential for future management of this pest. Gene expression studies could be considered as one of the key experimental approaches for such purposes. A suitable reference gene selection is fundamental for quantitative gene expression analysis and functional genomics studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Teng et al 75 reported elongation factor2 ( eEF2 ) as the most stably expressed gene in different developmental stages of Plutella xylostella . The expression stability of eEF2 in developmental stages and tissues was also documented in Agrilus planipennis 76 ; I. sexdentatus 43 ; Sogatella furcifera 77 ; Mythimna separata 63 , 78 ; Tuta absoluta 61 ; Hippodamia variegate 42 ; Spodoptera frugiperda 64 . However, Ponton et al 32 reported that the elongation factor was unsuitable for normalization of relative expression due to the different expression variability in different experimental conditions in Drosophila melanogaster .…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…Teng et al 75 reported elongation factor2 ( eEF2 ) as the most stably expressed gene in different developmental stages of Plutella xylostella . The expression stability of eEF2 in developmental stages and tissues was also documented in Agrilus planipennis 76 ; I. sexdentatus 43 ; Sogatella furcifera 77 ; Mythimna separata 63 , 78 ; Tuta absoluta 61 ; Hippodamia variegate 42 ; Spodoptera frugiperda 64 . However, Ponton et al 32 reported that the elongation factor was unsuitable for normalization of relative expression due to the different expression variability in different experimental conditions in Drosophila melanogaster .…”
Section: Discussionmentioning
confidence: 76%
“…Similarly, different developmental stages ( RPL32, RPS18 ) and different tissues ( RPS18 ) of Spodoptera frugiperda showed the most stable expression 64 , whereas RPS26 and RPL32 genes showed the same in Thermobia domestica 65 ; RPS11 , RPL28 , and RPL10 genes showed Tuta absoluta 58 ; RPS18 and RPL13 genes showed Rhopalosiphum padi tissues 66 . Sellamuthu et al 43 reported that RPS3 is stably expressed in the developmental stage, sex-specific and tissue-specific conditions in pine-feeding bark beetle, I. sexdentatus . Furthermore, RPL36 displayed stable expression in the developmental stage, sex-specific and tissue-specific conditions of Glenea cantor 67 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies of reference genes in insects are common. In coleoptera, reference gene screening has been performed in approximately twenty insect species, such as Dendroctonus valens , Harmonia axyridis , and Cerambycidae species , Monochamus alternatus, Anoplophora glabripennis ( Toutges et al, 2010 ; Rajarapu et al, 2012 ; Shi et al, 2013 ; Barros Rodrigues et al, 2014 ; Wang et al, 2014 ; Song et al, 2015 ; Tan et al, 2015 ; Feng et al, 2016 ; Rodrigues et al, 2017 ; Yang et al, 2018 ; Yang et al, 2020 ; Zhang et al, 2020 ; Zheng et al, 2020 ; Guo et al, 2021 ; Sellamuthu et al, 2021 ). And common reference genes for Coleoptera studies include ACT (actin), β-TUB (beta-tubulin), α-TUB (alpha-tubulin), RPs (ribosomal proteins), 18S rRNA (18S ribosomal RNA), 28S rRNA (28S ribosomal RNA), EF1-α (elongation factor1-α) and so forth ( Toutges et al, 2010 ; Zhang et al, 2020 ; Guo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%